ROLE OF LEVOFLOXACIN FOR TREATMENT OF CHRONIC SUPPURATIVE OTITIS MEDIA: SAMPLE OF IRAQI PATIENTS - Naji Sultan, Safaa Sahib; Alsaady, Malath Azeez (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: To evaluate levofloxacin efficiency for treatment of chronic suppurative otitis media in sample of Iraqi patients. Methods: This is a prospective study which includes 50 patients of different age groups diagnosed with CSOM. Aural toilet and otosporin ear drop performed in clinic, then levofloxacin prescribed as single oral tablet daily for 4-6 weeks. Patients were examined every 2 weeks for 8 weeks and then once by month for 6 months to evaluate the efficiency of treatment. Results: Forty patients (80%) showed complete dryness and healing. Discharge decreased upon the visits with more dryness observed after 4 weeks of treatment. Signs of healing and tympanic perforation closure apparently occur about 1 month from the initial treatment in 32 patients (80% of successful treatment). Culture sensitivity tests results were Pseudomonas aeruginosa and Klebsiella species in discharge materials. Conclusion: Levofloxacin is a safe and effective drug for the treatment of CSOM and promising treatment for CSOM in combination with aural toilet. The main species of microorganism detected were P. aeruginosa and Klebsiella.